How bargaining mediates wage determination: An exploration of the parameters of wage functions in a pooled time-series cross-section framework - Bernhard Kittel (Max-Planck-Institut für Gesellschaftsforschung, 2001)
The process of wage determination is mediated by the institutional framework of the labor market. Bargaining systems differ not only in their mode of governance, but also in the way that wages are related to unemployment, inflation, and productivity growth. Based on annual data for the period 1971-1996 from 20 OECD countries, the paper uses a pooled time-series cross-section model to show that bargaining modes affect the speed at which wages are adjusted and the extent to which macroeconomic factors affect wages. Contrary to the expectations of mainstream economics, uncoordinated bargaining does not turn out to be the most flexible mode. Pattern setting and peak-level coordination, if legally enforceable, are modes of labor market governance that are at least as flexible and responsive, if not more so. Hence these labor market institutions cannot be blamed for excessive rigidity. – – Der Lohnfindungsprozess ist abhängig von den institutionellen Rahmenbedingungen des Arbeitsmarktes. Lohnverhandlungssysteme unterscheiden sich nicht nur hinsichtlich der Interaktionsformen ihrer Akteure, sondern auch hinsichtlich der Art, wie Löhne auf Arbeitslosigkeit, Inflation und Produktivitätswachstum reagieren. Auf der Basis von jährlichen Daten von 20 OECD-Staaten für die Periode 1971-1996 zeigt der Aufsatz mit Hilfe einer Panel-Analyse, dass der Lohnverhandlungsmodus sowohl die Anpassungsgeschwindingkeit der Löhne als auch das Ausmaß des Effekts makroökonomischer Faktoren auf die Löhne beeinflusst. Im Gegensatz zur gängigen ökonomischen Erwartungen zeigt sich das nicht-koordinierte Lohnverhandlungssystem nicht als der flexibelste Modus. Sowohl Lohnführerschaft als auch dachverbandliche Koordinierung auf der Basis hoher Regierbarkeit führen zu mindestens ebenso oder flexibleren Anpassungsleistungen des Arbeitsmarktes. Hieraus folgt, dass diese Arbeitsmarktinstitutionen nicht als Ursachen exzessiver Rigidität herangezogen werden können.
Keywords: 300; Lohnverhandlungstheorie; Tarifpolitik; Schock; Lohnrigidität; Arbeitsmarktflexibilisierung; Schätzung; OECD-Staaten